PERLINDUNGAN HAK ANAK SEBAGAI PELAKU TINDAK PIDANA PENGANIAYAAN PADA PROSES REKONSTRUKSI - Mellenia, Greynia Septia; Gusman, Erry; Zulfiko, Riki (MIZAN, Jurnal Ilmu Hukum, 2024)
This study aims to examine children's rights in carrying out the reconstruction of cases of abuse carried out by investigators, the obstacles that are often faced by investigators in carrying out reconstruction, and the efforts of investigators to deal with obstacles when carrying out reconstruction, this study uses empirical juridical research, namely examining applicable legal provisions and what actually happens in society. As for the results of the first study, Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection regulates the protection of the rights of children who become suspects in criminal acts because criminal justice for children is not merely a punishment but for improvement. conditions, maintenance and protection of children and preventing repetition of acts by using constructive courts. Second, the obstacle in the process of reconstructing the crime itself is that ideally in carrying out the reconstruction of the crime it must be carried out at the scene of the incident. Because by carrying out the reconstruction of the crime at the scene of the case, it will make it easier for the suspect to carry out his actions thereby facilitating the examination. However, it is not uncommon for the reconstruction of a crime to be carried out at the scene of the actual incident. This is because there are obstacles from the community, whose emotions usually have not subsided due to cases that have happened to their families and their environment. Usually, in big cases and this worries the community, reconstruction of the crime is not carried out at the place where the case occurred. So that in cases like this the reconstruction of the crime is carried out at the scene determined by the investigator, and the third is that obstacles arising from the investigation process in overcoming obstacles that arise due to the loss of evidence can be prevented by providing information to the public. through legal counseling as well as to law enforcement agencies themselves and related agencies. In this way, it is hoped that the public will know more about the importance of evidence in the context of the case settlement process. Meanwhile, other obstacles can be overcome by increasing public legal awareness through legal counseling. This counseling does not have to be carried out in a formal setting but can be carried out informally by each member of the Police in their daily interactions in the community. So that this will bring citizens and the police closer together in a friendly and open relationship.